The impact of badminton on health markers in untrained females. Issue 11 (3rd June 2017) - Patterson, Stephen; Pattison, John; Legg, Hayley; Gibson, Ann-Marie; Brown, Nicola
ABSTRACT: The purpose of the study was to examine the health effects of 8 weeks of recreational badminton in untrained women. Participants were matched for maximal oxygen uptake (V̇O2max ) and body fat percentage and assigned to either a badminton ( n = 14), running ( n = 14) or control group ( n = 8). Assessments were conducted pre- and post-intervention with physiological, anthropometric, motivation to exercise and physical self-esteem data collected. Post-intervention, V̇O2max increased ( P < 0.05) by 16% and 14% in the badminton and running groups, respectively, and time to exhaustion increased ( P < 0.05) by 19% for both interventions. Maximal power output was increased ( P < 0.05) by 13% in the badminton group only. Blood pressure, resting heart rate and heart rate during submaximal running were lower ( P < 0.05) in both interventions. Perceptions of physical conditioning increased ( P < 0.05) in both interventions. There were increases ( P < 0.05) in enjoyment and ill health motives in the running group only, whilst affiliation motives were higher ( P < 0.05) for the badminton group only. Findings suggest that badminton should be considered a strategy to improving the health and well-being of untrained females who are currently not meeting physical activity guidelines.